(untitled) (REMUNOM, 2023)
Domestic violence against the elderly is defined as any action or omission that causes physical, psychological, sexual or financial harm to an elderly person. Domestic violence against the elderly is a serious public health problem, as it affects thousands of elderly people in Brazil. Therefore, this study analyzed domestic violence against the elderly and for that purpose it listed the practice of nurses in assisting elderly victims of domestic violence with a view to identification and prevention. The methodology used in this research was of a qualitative nature, with descriptive purposes, through a systematic bibliographical review in databases such as Scielo, PubMed and Google Scholar. Through this systematization, we sought to investigate the main strategies used by nursing professionals to face this problem. In the end, it was considered that nurses play an essential role in preventing violence against the elderly by providing guidance to the community on the rights of the elderly, risk factors and prevention strategies, in addition to working in collaboration with other health professionals to develop programs of health education and preventive interventions.